A new minute riffle beetle (Coleoptera: Elmidae: Pagelmis) from the Brazilian Amazon - Polizei, Thiago T. S.; Hamada, Neusa (Zootaxa, 2021)
The monotypic genus Pagelmis Spangler, 1981 was described from six thousand specimens of Pagelmis amazonica Spangler, 1981 collected with blacklight traps in Ecuador. For many years the known distribution of this genus was restricted to its type-locality, and recently it was recorded in Venezuela, Suriname and Brazil (Roraima State). Now, 40 years after the description of the genus, we describe the second Pagelmis species, based on male and female collected in the Amazon forest (Amazonas State, Brazil). With the description of the second species in the genus we provide an emended diagnosis of Pagelmis. Since adults of this genus were previously collected only in light traps, no habitat information was known. We collected adults of the new species in the first- and second-order streams with black, acidic water and sandy streambeds. The main substrates available in these streams were leaves and roots of riparian vegetation.